Daikenchuto (TU‐100) shapes gut microbiota architecture and increases the production of ginsenoside metabolite compound K. Issue 1 (10th February 2016) - Hasebe, Takumu; Ueno, Nobuhiro; Musch, Mark W.; Nadimpalli, Anuradha; Kaneko, Atsushi; Kaifuchi, Noriko; Watanabe, Junko; Yamamoto, Masahiro; Kono, Toru; Inaba, Yuhei; Fujiya, Mikihiro; Kohgo, Yutaka; et al.
Abstract: Many pharmaceutical agents not only require microbial metabolism for increased bioavailability and bioactivity, but also have direct effects on gut microbial assemblage and function. We examined the possibility that these actions are not mutually exclusive and may be mutually reinforcing in ways that enhance long‐term of these agents. Daikenchuto, TU‐100, is a traditional Japanese medicine containing ginseng. Conversion of the ginsenoside Rb1 (Rb1) to bioactive compound K (CK) requires bacterial metabolism. Diet‐incorporated TU‐100 was administered to mice over a period of several weeks. T‐RFLP and 454 pyrosequencing were performed to analyze the time‐dependent effects on fecal microbial membership. Fecal microbial capacity to metabolize Rb1 to CK was measured by adding TU‐100 or ginseng to stool samples to assess the generation of bioactive metabolites. Levels of metabolized TU‐100 components in plasma and in stool samples were measured by LC‐MS/MS. Cecal and stool short‐chain fatty acids were measured by GC‐MS. Dietary administration of TU‐100 for 28 days altered the gut microbiota, increasing several bacteria genera including members of Clostridia and Lactococcus lactis . Progressive capacity of microbiota to convert Rb1 to CK was observed over the 28 days administration of dietary TU‐100. Concomitantly with these changes, increases in all SCFA were observed in cecal contents and in acetate and butyrate content of the stool. Chronic consumption of dietary TU‐100 promotes changes in gut microbiota enhancing metabolic capacity of TU‐100 and increased bioavailability. We believe these findings have broad implications in optimizing the efficacy of natural compounds that depend on microbial bioconversion in general.